2009
DOI: 10.2174/138945009788982423
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Use in General Anaesthesia

Abstract: Dexmedetomidine is a potent and highly selective alpha(2)-adrenoreceptor agonist currently utilized for continuous infusion for sedation/analgesia in the intensive care unit (ICU). Dexmedetomidine offers remarkable pharmacological properties including sedation, anxiolysis, and analgesia with the unique characteristic to cause no respiratory depression. In addition it posses sympatholytic and antinociceptive effects that allow hemodynamic stability during surgical stimulation. Different from most of clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 56 publications
5
96
0
1
Order By: Relevance
“…As an anesthetic adjuvant, dexmedetomidine may reduce the dosage of opioids and propofol (31). In the present study, compared with propofol and remifentanil alone, dexmedetomidine was able to significantly decrease the mean infusion rate of propofol (101.5±8. )…”
Section: Discussionsupporting
confidence: 47%
“…As an anesthetic adjuvant, dexmedetomidine may reduce the dosage of opioids and propofol (31). In the present study, compared with propofol and remifentanil alone, dexmedetomidine was able to significantly decrease the mean infusion rate of propofol (101.5±8. )…”
Section: Discussionsupporting
confidence: 47%
“…DEX, even at a significantly high concentration, does not cause respiratory depression [10,11]. In our study, 2 patients Previous studies reported that use of DEX prior to general anesthesia lowered the required dose of thiopental and propofol by 37% and 80%, respectively [12,13].…”
Section: Discussionsupporting
confidence: 45%
“…a2-adrenoreceptor agonists are also expected to increase the release of atrial natriuretic peptide resulting in natriuresis. 6 The purpose of this experimental study was to evaluate the biochemical and histologic effects of dexmedetomidine on kidney IR injury in rats.…”
Section: Introductionmentioning
confidence: 99%